A shunt line metering system for irrigation wells - Hill, William C., author; Agricultural Experiment Station, Colorado State University, publisher (Colorado State University. Libraries, 1975)
The purpose of this project was to develop a metering system which could measure the ground water use in Colorado with the following constraints placed on the instrument. The system had to be versatile to function on the many different irrigation systems in the state. It had to be relatively inexpensive, durable, reliable, and accurate to within ± 7%. A shunt line meter design was selected due to its versatility and low cost. The main components of the system are a side contracted orifice plate, a shunt line, and small household type water meter. A side contracted orifice was used because it allows air and sediment to pass along the top and bottom of the pipe. The orifice edge was not bevelled to reduce machining costs. A magnetically coupled turbine meter was selected as the shunt line meter. It is accurate to within ± 2%, functions at low pressures, and passes sediment better than most meters. This is an accumulative flow meter which registers directly in total volume. The shunt line metering system is driven by the small pressure difference caused by the orifice plate in the irrigation pipe. This pressure differential diverts water into the shunt line, through the turbine meter and back into the irrigation pipe downstream of the orifice. The relationship of the metered shunt line flow to the total flow through the irrigation pipe was determined experimentally. The shunt, line-irrigation pipe relationship was obtained for a wide range of discharges, orifice sizes, and pipe sizes. This information allows immediate field installation and use without expensive on-site calibration. Thus the total water discharged from a well can be determined by reading the shunt line meter and referring to the appropriate shunt line-irrigation pipe relationship. Limited field studies to date indicate that this metering system is a viable means of measuring ground water use.
CER74-7SWCH-43.
May, 1975.
Keywords: Flow meters; Wells